Virtual colonoscopy: effect of computer-assisted detection (CAD) on radiographer performance. - Burling D; Moore A; Marshall M; Weldon J; Gillen C; Baldwin R; Smith K; Pickhardt P; Honeyfield L; Taylor S; Burling, D; Moore, A; et al. (Clinical Radiology, 2008)
Aim: To investigate the effect of a virtual colonoscopy (VC) computed-assisted detection (CAD) system on polyp detection by trained radiographers. Materials and Methods: Four radiographers trained in VC interpretation and utilization of CAD systems read a total of 62 endoscopically validated VC examinations containing 150 polyps (size range 5-50mm) in four sessions, recording any polyps found and the examination interpretation time, first without and then with the addition of CAD as a "second reader". After a temporal separation of 6 weeks to reduce recall bias, VC examinations were re-read using "concurrent reader" CAD. Interpretation times, polyp detection, and number of false-positives were compared between the different reader paradigms using paired t and paired exact tests. Results: Overall, use of "second reader" CAD significantly improved polyp detection by 12% (p<0.001, CI 6%,17%)) from 48 to 60%. There was no significant improvement using CAD as a concurrent reader (p=0.20; difference of 7%, CI -3%, 16%) and no significant overall difference in recorded false-positives with second reader or concurrent CAD paradigms compared with unassisted reading (p=0.25 and 0.65, respectively). The mean interpretation time was 21.7 min for unassisted reading, 29.6 (p<0.001) min for second reader and 19.1 min (p=0.12) for concurrent reading paradigms. Conclusion: CAD, when used as a second reader, can significantly improve radiographer reading performance with only a moderate increase in interpretation times.